IMPLEMENTATION OF THE IMLA METHOD IN LEARNING MAHARAH AL-KITABAH IN CLASS X RELIGION OF MA NURUL HUDA PRINGSEWU: Indonesia - Nada Shifa Afifatus Salsabila; Salamun, Salamun (Jurnal Pendidikan Bahasa Arab L-DHAD, 2023)
Maharah kitabah and writing skills are activities that aim to produce output in the form of writing. The place and method for expressing one's language that is not limited by space or time is writing. At the Nurul Huda Pringsewu Madrasah, most of the students are students who study at the Nurul Huda Pringsewu Islamic boarding school, as well as class X students, but the results of learning Arabic for class X students, especially in writing skill material, are lacking, even though in the learning process the teacher has used the appropriate method in this case the imla method. This study uses a descriptive method with the type of qualitative research, which uses data sources from interviews and observations, teachers and students in class X Religion at MA Nurul Huda Pringsewu whose students do not all come from Islamic education or Islamic boarding schools but some come from formal education. The implementation of the imla method at MA Nurul Huda Pringsewu using the types of imla' mandzur and imla' masmu' methods shows compatibility with the theory of imla' method implementation.